Crash-test dummy and pendulum impact tests of ice hockey boards: greater displacement does not reduce impact - Schmitt, K. U.; Muser, M. H.; Thueler, H.; Bruegger, O. (British Journal of Sports Medicine, 2018)
Background: One injury mechanism in ice hockey is impact with the boards. We investigated whether more flexible hockey boards would provide less biomechanical loading on impact than did existing (reference) boards.